Factor Analysis of Learning Difficulties in Independent Curriculum Science Learning in State Elementary Schools - Cynthia Azahra; M. Wahyudi (Science Journal Get Press, 2024)
Education plays an important role in national development, and improving educational quality has become a priority of the Indonesian government through the implementation of the Merdeka Curriculum, which provides schools with greater flexibility to design learning according to students’ characteristics and needs. However, learning difficulties in science subjects remain a challenge, influenced by factors such as ineffective teaching strategies, limited conceptual understanding among teachers, differences in students’ learning styles, and environmental conditions at home and school.This study employed a qualitative approach to explore learning difficulties experienced by students implementing the independent learning curriculum. The findings show that students face learning difficulties in three main aspects: social interaction, perception, and memory. These difficulties affect students’ ability to respond to teachers’ questions, academic performance, motivation, and self-confidence. The results indicate the need for more effective teaching strategies that emphasize repetition, memory reinforcement, and the reduction of learning distractions, supported by the role of teachers and a supportive learning environment to help students overcome these challenges.